Atypical Rearrangements in APL-Like Acute Myeloid Leukemias: Molecular Characterization and Prognosis - Guarnera, Luca; Ottone, Tiziana; Fabiani, Emiliano; Divona, Mariadomenica; Savi, Arianna; Travaglini, Serena; Falconi, Giulia; Panetta, Paola; Rapanotti, Maria Cristina; Voso, Maria Teresa (Frontiers in Oncology, 2022)
Acute promyelocytic leukemia (APL) accounts for 10–15% of newly diagnosed acute myeloid leukemias (AML) and is typically caused by the fusion of promyelocytic leukemia with retinoic acid receptor α (RARA) gene. The prognosis is excellent, thanks to the all-trans retinoic acid (ATRA) and arsenic trioxide (ATO) combination therapy. A small percentage of APLs (around 2%) is caused by atypical transcripts, most of which involve RARA or other members of retinoic acid receptors (RARB or RARG). The diagnosis of these forms is difficult, and clinical management is still a challenge for the physician due to variable response rates to ATRA and ATO. Herein we review variant APL cases reported in literature, including genetic landscape, incidence of coagulopathy and differentiation syndrome, frequent causes of morbidity and mortality in these patients, sensitivity to ATRA, ATO, and chemotherapy, and outcome. We also focus on non-RAR rearrangements, complex rearrangements (involving more than two chromosomes), and NPM1-mutated AML, an entity that can, in some cases, morphologically mimic APL.